Кольцевые структуры континентов Земли - Брюханов В. Н. Владимир Николаевич; Буш В. А. Вильям Артурович; Глуховский М. З. Марат Зиновьевич; Зверев А. Т. (Москва, Недра, 1987)
Авт. указаны на обороте тит. л.